Chewing lice of the genus Philopterus (Phthiraptera: Philopteridae) from drongos (Passeriformes: Dicruridae) - Sychra, Oldrich; Palma, Ricardo L.; Saxena, Arun K.; Ahmad, Aftab; Bansal, Nayanci; Adam, Costică (Zootaxa, 2011)
The chewing lice of the genus Philopterus parasitic on drongos (Dicruridae) are reviewed. Both sexes of the two species previously known from dicrurid hosts—P. trabecula (Piaget, 1880) and P. kalkalichi Ansari, 1955—are redescribed and illustrated. A new species, Philopterus petrescuae Adam is described from Dicrurus hottentottus from Indonesia. A lectotype for P. trabecula is designated. A record of Philopterus crassipes (Burmeister, 1838) from Dicrurus remifer (Temminck) is discussed and considered to be the result of straggling or contamination.